Parasitofauna de cachara cultivado em tanque-rede no rio Paraguai - Jeronimo, Gabriela Tomas; Ventura, Arlene Sobrinho; Pádua, Santiago Benites De [UNESP]; Satake, Fabiana; Ishikawa, Marcia Mayumi; Martins, Mauricio Laterça (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to describe the parasitic fauna of cachara (Pseudoplatystoma reticulatum) cultured in a net-cage in the Paraguai River, Brazil. Ten fish with mean weight of 598.0±81.3 g and total length of 38.6±1.6 cm were examined. All necropsied fish were parasitized by at least two species. Among them, Ichthyophthirius multifiliis (Ciliophora), Myxobolus sp. and Henneguya sp. (Myxozoa), Monogenoidea, Choanoscolex abscissus and Nominoscolex sudobim (Cestoda), Dolops carvalhoi (Crustacea), and Digenea were diagnosed. The protozoan Ichthyophthirius multifiliis was the most prevalent parasite.

O objetivo deste trabalho foi descrever a fauna parasitária de cachara (Pseudoplatystoma reticulatum) cultivado em tanque-rede, no rio Paraguai. Dez peixes com peso médio de 598,0±81,3 g e comprimento total médio de 38,6±1,6 cm foram examinados. Todos os peixes necropsiados apresentaram infestação por pelo menos duas espécies de parasitos. Entre os parasitos, foram encontrados Ichthyophthirius multifiliis (Ciliophora), Myxobolus sp. e Henneguya sp. (Myxozoa), Monogenoidea, Choanoscolex abscissus e Nominoscolex sudobim (Cestoda), Dolops carvalhoi (Crustacea) e Digenea. O protozoário Ichthyophthirius multifiliis foi o parasito com maior prevalência.
Parasitic fauna of cachara cultured in a net-cage in the Paraguay River, Brazil
Keywords: Ichthyophthirius multifiliis; Pseudoplatystoma reticulatum; controle sanitário; ictiofauna nativa brasileira; Monogenoidea; Ichthyophthirius multifiliis; Pseudoplatystoma reticulatum; sanitary control; Brazilian native fish fauna; Monogenoidea